Modulation of intercellular communication in macrophages: possible interactions between GAP junctions and P2 receptors - Fortes, F. S. A.; Pecora, Iracy Lea [UNESP]; Persechini, P. M.; Hurtado, S.; Costa, V; Coutinho-Silva, R.; Braga, MBM; Silva-Filho, F. C.; Bisaggio, R. C.; Farias, F. P. de; Scemes, E.; Carvalho, A. C. C. de; et al. (Company of Biologists Ltd, 2004)
Gap junctions are connexin-formed channels that play an important role in intercellular communication in most cell types. In the immune system, specifically in macrophages, the expression of connexins and the establishment of functional gap junctions are still controversial issues. Macrophages express P2X(7) receptors that, once activated by the binding of extracellular ATP, lead to the opening of transmembrane pores permeable to molecules of up to 900 Da. There is evidence suggesting an interplay between gap junctions and P2 receptors in different cell systems. Thus, we used ATP-sensitive and -insensitive J774.G8 macrophage cell lines to investigate this interplay. To study junctional communication in J774-macrophage-like cells, we assessed cell-to-cell communication by microinjecting Lucifer Yellow. Confluent cultures of ATP-sensitive J774 cells (ATP-s cells) are coupled, whereas ATP-insensitive J774 cells (ATP-i cells), derived by overexposing J774 cells to extracellular ATP until they do not display the phenomenon of ATP-induced permeabilization, are essentially uncoupled. Western-blot and reverse-transcription polymerase chain reaction assays revealed that ATP-s and ATP-i cells express connexin43 (Cx43), whereas only ATP-s cells express the P2X(7) receptor. Accordingly, ATP-i cells did not display any detectable ATP-induced current under whole-cell patch-clamp recordings. Using immunofluorescence microscopy, Cx43 reactivity was found at the cell surface and in regions of cell-cell contact of ATP-s cells, whereas, in ATP-i cells, Cx43 immunoreactivity was only present in cytosolic compartments. Using confocal microscopy, it is shown here that, in ATP-s cells as well as in peritoneal macrophages, Cx43 and P2X(7) receptors are co-localized to the membrane of ATP-s cells and peritoneal macrophages.
Keywords: J774 macrophage-like cells; Connexin43; P2X(7) receptor; ATP; gap junction